Repeated axial compressive performance of GCFST columns: Test investigation and numerical analysis - Cun Hui; Jianwei Zhang; Yun Cao; Xiang Chen; Ran Hai (Scientific Reports)
Abstract Geopolymer concrete (GC) is green and environmentally friendly. In order to comprehensively study the mechanical properties and influence mechanism of geopolymer concrete-filled steel tubular (GCFST) columns under various working conditions, this study takes the strength grade of geopolymer concrete, length-diameter ratio and wall thickness of steel tube as design parameters. Eight GCFST columns are designed and the compressive performances are conducted under repeated axial compression. The load–displacement curve, the skeleton curve, the characteristic load and displacement, the ductility, and the energy dissipation were analyzed. Furthermore, the numerical analysis models were established through finite element software and the test results were compared with the simulation results to verify the accuracy of the finite element model. The results indicate that under different length-diameter ratios, the variation trends of the load–displacement curves for the specimens are slightly different, while the stiffness degradation curves present similar variation laws. The design parameters have significant effects on the bearing capacity, average compressive force, and energy dissipating capacity of the specimens. The simulation results are in good agreement with the experimental results. Research results show the excellent bearing capacity of GCFST columns and the precision of finite element calculation results, which can provide a reference for related experimental research.